VD_FINDINFO MP / 2022 / 5 vom 27. September 2022 - VD Tribunal cantonal (2022)
DÉBAUCHAGE, CLAUSE CONTRACTUELLE, PROHIBITION DE CONCURRENCE | 321a al. 1 CO, 321a al. 4 CO, 340 CO, 2 LCD, 4 let. c LCD, 6 LCD, 152 al. 2 CPC (CH), 229 CPC (CH), 90 CPC (CH)